2021
DOI: 10.1186/s12909-021-02574-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among perceived learning, challenge and affect in a clinical context

Abstract: Background Challenge, sometimes perceived as stress, may be beneficial or detrimental to learning but the circumstances when it may be beneficial are not clear. This study looks at the association of challenge with perceived learning and how this might be influenced by affect, context or the type of learning. Method The participants, medical students in their first years of experiential clinical exposure, rated specified learning episodes (LEs) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Unlike other studies which reported that clinical learning aggravated distress [ 3 , 18 , 35 , 36 ], in our study, the nursing students identified clinical learning stress levels as moderate (mean = 3.13; SD = 0.50), while their levels of psychological distress were relatively low. It is possible that stressors related to clinical learning are eustresses [ 37 ]. The use of positive coping strategies, such as support-seeking and problem-solving, to cope with the stress in clinical learning might also contribute to relieve the distress.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies which reported that clinical learning aggravated distress [ 3 , 18 , 35 , 36 ], in our study, the nursing students identified clinical learning stress levels as moderate (mean = 3.13; SD = 0.50), while their levels of psychological distress were relatively low. It is possible that stressors related to clinical learning are eustresses [ 37 ]. The use of positive coping strategies, such as support-seeking and problem-solving, to cope with the stress in clinical learning might also contribute to relieve the distress.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a potential relationship between VA and cognitive load could result in a decreased perception of difficulty for high VA students when studying for the course; however, perceived difficulty does not necessarily correlate with SAL. In fact, tasks with higher perceived difficulty can actually have a positive effect on students' motivation to learn (Rudland et al, 2021), which would theoretically increase their reliance on deep approaches to learning. In future studies, it would be interesting to delve further into the potential relationships between VA, SAL, and cognitive load through studies using neurofeedback approaches such as electroencephalography and functional near-infrared spectroscopy, or other electrophysiological measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Rudland et al reported positive correlations between perceived learning and challenges within certain circumstances. 13 A challenge is defined as “Something that needs skills, energy and or determination to deal with or achieve”. 14 Positive challenges are eustress, a form of positive emotions that result in better cognitive tasks performance like hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%